Virtual Reality Bank: A Novel Banking Experience in Immersive World - Rasanji, Vidushika; Kumarasinghe, Nikeshi; Pethangoda, Rumal; Karunarathna, Vidura; Rodrigo, Ranga (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais do XXVI Simpósio de Realidade Virtual e Aumentada, 2024)
As Virtual Reality (VR) technology continues to advance and wide-spread through various industries, the potential of immersive technologies in the banking sector has also begun to be acknowledged more commonly. VR banking, a 3D bank environment developed in an immersive world to provide customers with bank services, has the potential to substantially enhance the customer experience. However, a clear insight into an end-to-end pipeline for developing a banking system in VR is yet to be presented. This paper presents a novel VR banking system that facilitates users with personalized full-body avatars for representation within a VR bank, a speech-to-text integration for providing user information for bank services, and real-time dual avatar interaction and communication with a bank employee. Through a subjective survey, we evaluate the performance of the proposed facilitates and the overall VR bank application in comparison to mobile and physical banking. Our study reveals that integrated features have successfully achieved their expected level of performance and contributed to creating a convenient, inventive, personalized, and accessible VR bank application.